Ekslibris Eugenio Rosasco / Dolatowski. - Dolatowski, Zbigniew (1927-2001) ([wydawca nieznany], 1968)
Ukoronowany herb wokoło ćmy, u dołu napis: Ekslibris Eugenio Rosasco, pod wyobrażeniem autograf artysty i data.